2016
DOI: 10.1080/23269995.2016.1253271
|View full text |Cite
|
Sign up to set email alerts
|

Dehumanisation in religious and sectarian violence: the case of Islamic State

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the final experiment, we extend our thesis to hypothesize that when victims have strongly reduced human attributes, morally motivated perpetrators may be motivated to humanize victims to make their moral violence meaningful (23). To do so, we drew on previous research that found that people are ascribed reduced human attributes when they are unconscious (50).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final experiment, we extend our thesis to hypothesize that when victims have strongly reduced human attributes, morally motivated perpetrators may be motivated to humanize victims to make their moral violence meaningful (23). To do so, we drew on previous research that found that people are ascribed reduced human attributes when they are unconscious (50).…”
Section: Methodsmentioning
confidence: 99%
“…Recent ethnographic and historical analyses, and classical works on the evolution of cooperation and the sociology of crime, indicate that descriptively, many perpetrators feel their violence is righteous and that their victims deserve what is coming to them. The husband who avenges the murder of his wife, the vigilante who cripples criminals, the soldier who kills the enemy, the public that votes for capital punishment, and even the suicide terrorist who detonates a bomb-all may see violence as morally justified, obligatory, and even praiseworthy (16)(17)(18)(19)(20)(21)(22)(23). Meanwhile, recent philosophical analyses have argued that the logic of dehumanization is inconsistent with perpetrators' actions.…”
mentioning
confidence: 99%
“…In this example, dehumanisation is reflected in the alleged resemblance between the Yazidi people and the devil as non-human beings and in the view of women as spoils of war, which shows an objectification of human beings (Jasko et al, 2020). While the statements by Abu Jihad reflect dehumanisation of the victim, there are indications of self-dehumanisation when Abu Jihad considers himself as a tool of Allah (Kizilhan & Cavelius, 2016b;Ramsay, 2017). Despite these observations of different kinds of dehumanisation, it is important to emphasise that ISIS ideology draws on a rhetoric paying much attention to the 'believer vs. non-believer' dichotomy (Ramsay, 2017;Thompson, 2017).…”
Section: Dehumanisation and Sociological Mechanismsmentioning
confidence: 99%
“…While the statements by Abu Jihad reflect dehumanisation of the victim, there are indications of self-dehumanisation when Abu Jihad considers himself as a tool of Allah (Kizilhan & Cavelius, 2016b;Ramsay, 2017). Despite these observations of different kinds of dehumanisation, it is important to emphasise that ISIS ideology draws on a rhetoric paying much attention to the 'believer vs. non-believer' dichotomy (Ramsay, 2017;Thompson, 2017). Moreoever, the explanatory approaches which ascribe much importance to dehumanisation can be challenged in many other ways.…”
Section: Dehumanisation and Sociological Mechanismsmentioning
confidence: 99%
“…While IS itself seems to embrace a radically Manichean stance, famously announcing its eradication of the “grey zone” and the “division of the world in two camps,” 12 and consistently uses derogatory or dehumanizing labels to name the Shi’a Muslims (“Rafidi swine,” “filthy pigs,” etc. ; read Ramsay, 2016), the group nonetheless articulates a typical conspiratorial narrative that strictly followed the characteristics of the genre. As such, IS rearticulated a significant conspiratorial tradition in Salafi-jihadi thought that can be traced back to (at least) the writings of Sayyid Qutb, whose radical pamphlets “Our Struggle Against the Jews” (1950) and “Milestones” (1964) depicted a world where Muslims are trapped in a state of “ignorance” ( jahiliyyah ) caused by the combined actions of non-Muslim groups (above all the West) and hypocrite individuals ( munafiqun ) deceitfully pretending to be Muslims.…”
Section: Conspiratorial Narratives In Action: Three Casesmentioning
confidence: 99%